Composition and annealing effects in polythiophene/fullerene solar cells - Choulis, Stelios A.; Kim, Youngkyoo; Nelson, Jenny K. (My University, 2005)
We have fabricated organic solar cells with blends of regioregular poly(3-hexylthiophene) (P3HT) and 1-(3-methoxycarbonyl)-propyl-1-phenyl-(6,6) C 61 (PCBM) as electron donor and electron acceptor, respectively. Blend composition and device annealing effects were investigated with optical absorption and photoluminescence spectroscopy, atomic force microscopy, photocurrent spectroscopy, and current-voltage characteristic measurements on devices under monochromatic or air mass (AM) 1.5 simulated solar light illumination. The highest efficiency was achieved for the 1:1 (P3HT:PCBM) weight ratio composition. The good performance is attributed to an optimized morphology that enables close intermolecular packing of P3HT chains. Inferior performance for the 1:2 composition is attributed to poorer intermolecular packing with increased PCBM content, while phase segregation on a sub-micron scale was observed for the 1:4 composition. The power conversion efficiency (AM 1.5) was doubled by the thermal annealing of devices at 140°C to reach a value of 1.4%
Keywords: Solar cells; Fullerenes; Photoluminescence; Atomic force microscopy; Polychlorinated biphenyls